1987
DOI: 10.1007/bf02330592
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocytes in ankylosing spondylitis and the influence of sulphasalazine treatment

Abstract: Twenty-nine patients with ankylosing spondylitis (AS) were studied in an attempt to evaluate the role of T lymphocytes in this disease and a possible influence of treatment. The proportions of various T cell subpopulations in blood were assessed with monoclonal antibodies. Before treatment the proportions of Leu-4+ cells and Leu 3a+ cells were decreased while Leu-2a+ lymphocytes appeared in normal proportions. Leu-7+ cells appeared in increased proportions. An increased proportion of Leu-M1 positive cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Reductions in none, one, two or all three of the IgA, IgG, or IgM classes have been reported3 [49][50][51][52][53][54][55][56][57][58][59][60][61][62] Six of our patients had increased serum IgA anti-gliadin antibody levels. The serum levels of IgA anti-gliadin antibodies decreased significantly during SASP therapy.…”
Section: Discussionmentioning
confidence: 63%
“…Reductions in none, one, two or all three of the IgA, IgG, or IgM classes have been reported3 [49][50][51][52][53][54][55][56][57][58][59][60][61][62] Six of our patients had increased serum IgA anti-gliadin antibody levels. The serum levels of IgA anti-gliadin antibodies decreased significantly during SASP therapy.…”
Section: Discussionmentioning
confidence: 63%
“…There is strong evidence for the involvement of humoral and cell-mediated immunity in the pathogenesis of AS, though investigations on abnormalities in immune cell numbers in peripheral blood [15][16][17], cytokine production [7,8,18] and occurrence of certain antibodies to different microbes [2,19,20] show conflicting results. It should be considered that there is a wide diversity of presenting symptoms in AS, and clinical expression varies a lot [21].…”
Section: Discussionmentioning
confidence: 99%
“…A study using nuclear microprobe technology measured the cellular storage of iron in granulocytes and platelets of 29 patients with AS, and found high levels of iron in granulocytes and platelets (12). Another two studies of blood cells in patients with AS also found that iron accumulation was significant in granulocytes and platelets in patients with AS (13,14). A case-control study of 30 patients with AS and 147 age -and sex-matched healthy controls found that iron intake was higher in patients with AS and that iron accumulation was significant in patients with AS (15).…”
Section: Introductionmentioning
confidence: 99%